Another Pictish cross-of-arcs: an old find from Shetland re-interpreted - Ritchie, Anna (Proceedings of the Society of Antiquaries of Scotland, 2018)
A fragment of carved stone known as ‘Lerwick’ (NMS X.IB.19) is argued to have come, most probably, from the Pictish levels at Jarlshof, Dunrossness, Shetland, sometime before June 1861. The stone bears part of a Pictish crescent symbol on one side and part of a cross-of-arcs embellished with decorated lentoid forms on the other. The symbol-bearing cross-slab from which the fragment comes probably dates to the 7th century and may have stood in or near a churchyard at Jarlshof. It is compared with the cross-slabs from Papil and Bressay and with fragments of similar Shetland stones, and its place in the development of the cross-of-arcs is discussed.